Pengaruh Destination Image, Smart Tourism Technology Dan Authenticity Terhadap Revisit Intention Dengan Memorable Tourist Experience Sebagai Variabel Intervening: Studi Pada Kawasan Wisata Kuliner Kampung Bustaman Di Kota Semarang - Layla Widjaya Prarahesti; Harry Soesanto (Faculty of Economics and Business Diponegoro University, 2025)
This study examines the factors influencing Revisit Intention at Kampung Bustaman culinary tourism destination, focusing on the effects of Destination Image, Authenticity, and Smart Tourism Technology, with Memorable Tourist Experience as an intervening variable. A sample of 125 visitors was surveyed, and data analysis was conducted using Structural Equation Modeling (SEM) in AMOS. The findings reveal that Destination Image, Authenticity, and Smart Tourism Technology positively influence Memorable Tourist Experience, with Authenticity having the strongest impact. Moreover, Memorable Tourist Experience positively affects Revisit Intention. While Smart Tourism Technology and Authenticity directly impact Revisit Intention, Destination Image does not have a direct effect.